The Role Of Student Da’wah Institutions In Improving Non-academic Achievements In The Faculty Of Social And Political Sciences, Mulawarman University: Peran Lembaga Dakwah Kemahasiswaan Dalam Meningkatkan Prestasi Non Akademik Di Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Mulawarman - Fauzi, Ahmad; Abdullah, Zulkifli (Progress In Social Development, 2021)
ABSTRACT: This study aims to identify and describe the role of the Student Da'wah Institute of the Faculty of Social and Political Sciences, Mulawarman University in contributing to improving the non-academic achievements of FISIP Mulawarman University students and to identify and describe the supporting and inhibiting factors of the Student Da'wah Institute (LDK) FISIP Mulawarman University in improving achievement. Non-Academic. The data collection technique is purposive sampling and the data analysis used in this research is descriptive qualitative. The results of this study indicate the role of LDK FISIP Mulawarman University in improving students' non-academic achievements, has three roles, namely the role of LDK FISIP as Education (Dakwah Education), the role of LDK FISIP as a facilitator, and the role of LDK FISIP as a motivator. ABSTRAK: Penelitian ini ditujukan untuk mengetahui dan mendekskripsikan peran Lembaga Dakwah Kemahasiswaan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman dalam berkontribusi meningkatkan prestasi Non Akademik mahasiswa FISIP Universitas Mulawarman dan untuk mengetahui dan mendeskripsikan faktor pendukung dan penghambat Lembaga Dakwah Kemahasiswaan (LDK) FISIP Universitas Mulawarman dalam meningkatkan prestasi Non Akademik. Adapun Teknik pengumpulan data adalah purposive sampling dan analisis data yang di gunakan dalam penelitian ini adalah deskriptif kualitatif. Hasil penelitian ini menunjukkan peran LDK FISIP Universitas Mulawarman dalam meningkatkan prestasi Non Akademik Mahasiswa, memiliki tiga peran yaitu Peran LDK FISIP sebagai Edukasi (Pendidikan Dakwah), Peran LDK FISIP sebagai Fasilitator dan Peran LDK FISIP sebagai Motivator.